2016
DOI: 10.1159/000443609
|View full text |Cite
|
Sign up to set email alerts
|

High Level of Agreement between Electronic and Paper Mode of Administration of a Thyroid-Specific Patient-Reported Outcome, ThyPRO

Abstract: Introduction and Purpose: Use of electronic questionnaires to collect health-related quality-of-life data has evolved as an alternative to paper questionnaires. For the electronic questionnaire to be used interchangeably with the validated paper questionnaire, measurement properties similar to the original must be demonstrated. The aim of the present study was to assess the equivalence between the paper version and the electronic version of the thyroid-related quality-of-life questionnaire ThyPRO. Methods: Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…It takes 5-7 minutes to complete. The scores may be graded as mild (score of 6-10), moderate (score of [11][12][13][14][15], severe (score of [16][17][18][19][20], and very severe (score of 21-27). 5 The PHQ-9 is a multipurpose instrument that assists in the screening and measurement of depressive symptoms within the past 2 weeks.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…It takes 5-7 minutes to complete. The scores may be graded as mild (score of 6-10), moderate (score of [11][12][13][14][15], severe (score of [16][17][18][19][20], and very severe (score of 21-27). 5 The PHQ-9 is a multipurpose instrument that assists in the screening and measurement of depressive symptoms within the past 2 weeks.…”
Section: Measurementsmentioning
confidence: 99%
“…Care is needed when migrating questionnaires to electronic formats to ensure that measurement equivalence with the original is demonstrated and that the measurement characteristics of the scale remain unchanged. 11 The available research on measurement equivalence mainly aimed to examine the factors influencing the validity of the results when migrating from paper to electronic formats, the operability of electronic versions, and questionnaires regarding somatic diseases and health conditions, [12][13][14][15] but direct comparisons between electronic and paper versions of psychometric questionnaires are rare. These studies showed that the demographic characteristics of the respondents and the management model of the app would affect the measurement results of the electronic versions.…”
Section: Introductionmentioning
confidence: 99%
“…For a more accurate investigation in future studies, the serum levels of Selenium should also be investigated before including the patients in the study, because Selenium defficiency could be a major factor that contributes to a higher benefit of Selenium-supplementation therapy in autoimmune thyroiditis patients. For a better compliance from the patients and a more facile gathering of data from the questionnaire, we recommend implementing an electronic version of the questionnaire, as data from recent studies indicated this could improve the process of researching the health-related quality of life aspects [16].…”
Section: Discussionmentioning
confidence: 99%
“…Surveys are considered mode equivalent when participants give the same responses to the same questions administered by different modes . Previous reports showed that such differences were minimal between online and paper surveys, even when respondents had to report sensitive behaviours …”
Section: Advantagesmentioning
confidence: 99%